DAMPAK PERUBAHAN MATA PENCAHARIAN TERHADAP STRUKTUR SOSIAL MASYARAKAT NAGARI KOTO BERINGIN KEC. TIUMANG KAB. DHARMASRAYA - Dilla Malinia; Irwan Irwan; Sri Rahmadani (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
AbstractOne of the villages that has very good potential in the plantation sector. In general, the people used to make a living as rubber farmers. In 2012 the community changed their livelihood to oil palm plantations. This has an impact on the livelihood and social structure of the community due to changes in livelihoods. The purpose of this study is to analyze the livelihood and social structure of rural communities due to changes in livelihoods in Nagari Koto Beringin, Tiumang District, Dharmasraya Regency. This study used a qualitative approach, with data collection methods through in-depth interviews, observation and document studies. The data analysis model uses the Miles and Huberman model, namely through the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study show that changes in livelihoods have an impact on the livelihood and social structure of oil palm smallholders. Changes in the livelihood structure that occur in oil palm farmers are the addition of agricultural land, additional income in services and additional income in trade. In addition, there are also changes in the social structure, such as doing mutual cooperation, a sense of mutual assistance and higher concern. The novelty in this study is the social-based livelihood structure.